Pengembangan Media Pembelajaran Chatbot Berbasis Web Dalam Pembelajaran IPA SMP Untuk Meningkatkan Keterampilan Berpikir Kreatif Siswa - Nabillah, Zulva; Rusdianto; Ridlo, Zainur Rasyid (UNIB Press, 2024)
The purpose of this study is to describe the validity, practicality, and effectiveness of the results of the development of chatbot media tailored to the indicators of creative thinking skills to improve students' creative thinking skills. This research includes Research and Development which uses the ADDIE model (analysis, design, development, implementation, evaluation). Data collection was obtained from media validation forms, implementation observations, student response questionnaires, and tests (pretest and posttest). The results of chatbot media validation from three validators were 84.48% with a valid category. The results of the practicality of chatbot media from three observers were 93.23% with a very practical category. The results of the effectiveness of chatbot media from the N-gain results were 0.72 with a high category and student responses obtained 84.09% with a very good category. Based on the results of the study, chatbot media is valid and practical to be implemented in science learning and can improve students' creative thinking skills.